Cover Image. Issue 2 (1st March 2018) - Kim, S. W.; Jun, J. W.; Giri, S. S.; Chi, C.; Yun, S.; Kim, H. J.; Kim, S. G.; Kang, J. W.; Park, S. C.
Abstract : The cover image, by Sang Wha Kim et al., is based on the Rapid Communication First report of carp oedema virus infection of koi (Cyprinus carpio haematopterus) in the Republic of Korea, DOI: 10.1111/tbed.12782 .